Tuberculosis and its Control in Indonesia - A.S. Gunardi (Paediatrica Indonesiana, 1975)
Based on a tuberculosis prevalence survey with the assistance of WHO in 1962 - 1965 in the areas fogyakarta and Malang where were found a prevalence of tuberculin sensitivity of 40,6% at the age 10-14 years, a prevalence of bac- teriologically confirmed cases of 0.6% and those with pulmonary shadows 3.6%, a workshop in Ciloto was hold (January 1969), with the following results :a. BCG vaccination without prior tuberculin test to children of 0-14 years of age.b. Case finding and treatment to those with sputum â€afbâ€ positive.c. Health education to the people.In Pelita I priority was given to BCG vaccination with a target of 55 million of which a 75% coverage will be expected particularly in Java and Bali.For Pelita II BCG vaccination policy will be changed. To achieve a more realistic target and to have the most susceptible (high risk) ages vaccinated, every child should have a recent BCG vaccination before entering puberty and to vaccinate children early in life, 0-1 year. Only primary vaccination will be done during Pelita II while revaccination will be performed in Pelita III. As performers will be the smallpox vaccinators in a simultaneous vaccination programme with other vaccines.Case finding and treatment, and Health education will be improved in Pelita II because the health infra structure (organization) and community participation was below expectation in Pelita I; it will be integrated into the existig health activities. Treatment will only be given to patients with bacteriologically confirmed sputum, and free of charge.